Purple soil inheritance and source of parent rock material and tectonic background in the Sichuan Basin, China - Yizhou Peng; Grigorieva Iya Yu (Geology, Ecology, and Landscapes)
The parent rock inheritance of the purple soils in the Sichuan Basin is evident, and this is due to factors that are directly related to the parent rocks’ characteristics. Fundamentally, the nature of purple soils is determined by the lithology, chemical composition, weathering, and soil formation of parent rocks, whereas the provenance, and tectonic context of rocks during their diagenesis have a significant influence on their rock attributes. In this study, rocks from four sedimentary layers of the Cretaceous and Jurassic eras – k1c, J3p, J3s, J2s in the Sichuan Basin – as well as the overlying soils were examined, and experimental determinations of the samples’ physical characteristics and chemical elemental composition were made to confirm the parent rock inheritance of purple soils. The essential weathering indices ICV, CIAcorr, WIP, and Na/K were used to study the weathering characteristics of the rocks and soils, and the A-CN-K ternary diagram was used to assess the weathering trends of the rocks. The findings demonstrate that purple soil exhibits significant parent rock inheritance due to its rapid physical soil formation process and weak chemical weathering process. That the rocks of the four sedimentary layers in the study area have all reached a moderate degree of weathering, their original source components are quartzose sedimentary which may have been derived from feldspar source rocks. The tectonic background of the source rocks may be mainly continental arc and active continental margin environment, there may be an oceanic arc tectonic environment.